User satisfaction in child and adolescent mental health service: Comparison of background, clinical and service predictors for adolescent and parent satisfaction - Yngvild Arnesen; Kjersti R. Lillevoll; Børge Mathiassen (Health Expectations, 2023)
Abstract Background and Objective To improve quality, child and adolescent mental health services (CAMHS) are expected to quantify families' views on healthcare with user satisfaction measures. As little is known about what influences satisfaction in CAMHS, this study aimed to examine predictors of adolescents' and parents' user satisfaction. Methods Data from 231 adolescents and 495 parents in treatment at an outpatient clinic who returned a user satisfaction measure, the Experience of Service Questionnaire (ESQ), was analyzed. Registry data on background, clinical and service characteristics were predictors for the ESQ factors general satisfaction, satisfaction with care and satisfaction with environment. Results In regression models, satisfaction with care for adolescents (r2 = .12) was significant and was predicted by low parent‐self‐reported mental health burden and low clinician‐rated overall symptom burden at intake. For parents, regression models for general satisfaction (r2 = .07), satisfaction with care (r2 = .06) and satisfaction with environment (r2 = .08) were significant. Parents general satisfaction was predicted by higher levels of hyperactivity, less family stress and longer travelling distances to the service. Satisfaction with care for parents was predicted by higher levels of hyperactivity at intake and longer travelling distances. Satisfaction with environment for parents was more likely if the adolescents was a boy, with low levels of family stress and longer travelling distances. Conclusion Predictors for adolescent and parent user satisfaction in CAMHS differ. Hence, to improve quality CAMHS should enhance focus on collaborative practice with parents, and person‐centred care for adolescents with moderate to severe mental health illness. Patient or Public Contribution Representatives from the hospitals' youth panel and the non‐governmental organization called The Change Factory have been consulted regarding study design and results.